Blockchain Integration in Agriculture for Transparent Farm-to-Fork Supply Chains: Leveraging IoT and Decentralized Identity for Enhanced Traceability and Security - Soy Aakansha; Balkrishna Sutar Manisha (SHS Web of Conferences)
The main agricultural research problem addressed by this study involves the supply chain transparency inadequacies and operational inefficiencies that stem from data verification problems and trust issues as well as real-time monitoring limitations. Advanced cryptographic techniques, along with blockchain technology serve as the solution for supply chain enhancement throughout this research study. To address fundamental agricultural supply chain problems PBFT, DID, ZKP, SHA-256 Hashing and MQTT protocol joined together with PBFT to establish a solution for the sector. The PBFT consensus algorithm allows the system to reach dependable results even with faulty node distribution of up to 33% where the average delay remains below 500 ms. DID enables stakeholders to manage secure identities across the supply chain in a way which both consolidates trust and maintains accountability throughout the system. ZKP protects transaction confidentiality by showing validity evidence while maintaining secret transaction information which ensures secure data verification. Weaknesses in data can be prevented through the use of SHA-256 hashing which produces secure cryptographic hashes with a 99.9% error detection rate for integrity protection. MQTT protocol maintains a fast data transmission speed of 200 milliseconds to supply real-time monitoring through its structure. Blockchain showed a performance of 25 transactions per second and smart contracts needed on average 350 milliseconds to execute after technology integration. The innovative method merges various technologies effectively to enhance both data transparency and security and storage capabilities and trustworthiness of agricultural systems.